An Analysis of the Effects on Application of Management Accounting Information Systems and Quality Management Accounting Information - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The study aims Drove empirically; (!J the influence of the business environment for the al?plication of management accounting information systems; (ii) the intDnce o ethics on the application of management accounting information systems; iii the influence of organizational culture on the implementation of management accounting ifll·mation systems; allCI (iv) the effect of the ap lication of management accounting information system n the uali of management accounting information. Th motivation of this study due to a phenomenon of having an integration on management accounting information system whereby the information generated is not qualified, as well as the uncertainty of business environment, ethics and organizational culture which are yet to have optimal conditions. The method used is explanatory research with a survey approach, using a statistical tool of SEM Partial Linear Regression, with the aif,I to obtain facts concerning the occurance ofyhenomena, seek actual and systematic information on th application of management accounting information systems, and the ual' of accounting informatio management. The results showed that all variable of the business environment, ethics, organizational culture affect the application of accounting information management system; and the application of management accounting information system affects the quality of information management accounting.